The Effect of Organizational Rewards and Commitment on Employee Performance with Industrial - Dias Pipit Chusairy; Djoko Soelistya (LP2M IAIN Palopo, 2024)
This research was carried out with the aim of determining the influence of rewards, organizational commitment to employee performance mediated by industrial relations.This study uses a quantitative method, with a sample of 100 respondents analyzed through the SmartPLS program and produces findings that (1) rewards have a direct effect on employee performance; (2) Organizational commitment has a direct effect on employee performance; (3) Rewards have a direct effect on industrial relations; (4) Organizational commitment has a direct effect on industrial relations; (5) Industrial relations have a direct effect on employee performance and (6) Industrial relations are not needed as mediation, the direct influence of rewards is more dominant than indirect influence, so it is also called partial mediation, while (7) Industrial relations have an influence as mediation, the direct influence of organizational commitment is not dominant, this shows that Industrial Relations Has a Full Mediation Role.